2001
DOI: 10.1089/107555301300328179
|View full text |Cite
|
Sign up to set email alerts
|

Surveys of Complementary and Alternative Medicine: Part II. Use of Alternative and Complementary Cancer Therapies

Abstract: The second part of this series on surveys of complementary and alternative medicine (CAM) in the United States provides a "point-of-information" summary of the studies on patients with cancer and their use of CAM therapies. Surveys of patients with cancer were the precursors of the recent wave of studies on CAM prevalence and use. Three tables summarize the findings from a total of 18 surveys categorized by Childhood Cancer, Adult Cancer, and Breast Cancer studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 17 publications
2
37
0
3
Order By: Relevance
“…Previous reviews of the wider literature on CAM use across multiple cancer diagnoses have also found considerable variation across studies. 17,18 The variation in prevalence rates may be a consequence of the varied definitions of CAM use utilised in the original studies. For example, in our primary studies the reported time period over which CAM use is assessed ranged from 'current' CAM use (presumably more akin to incidence than prevalence) through CAM use since diagnosis (a varied time for different participants)/over the past 4 weeks-12 months, to any CAM use ever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews of the wider literature on CAM use across multiple cancer diagnoses have also found considerable variation across studies. 17,18 The variation in prevalence rates may be a consequence of the varied definitions of CAM use utilised in the original studies. For example, in our primary studies the reported time period over which CAM use is assessed ranged from 'current' CAM use (presumably more akin to incidence than prevalence) through CAM use since diagnosis (a varied time for different participants)/over the past 4 weeks-12 months, to any CAM use ever.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews on the subject need up-dating and do not provide detailed information focused on CAM use in prostate cancer. [16][17][18] Currently, this makes it difficult to have confidence in assertions about the prevalence of CAM use in prostate cancer. Furthermore, a comprehensive up-to-date review would provide useful information for oncologists that could aide their communication with patients about CAM, inform the research community as to gaps and inconsistencies in this literature and possibly identify new research areas.…”
Section: Introductionmentioning
confidence: 99%
“…Although complementary therapies are commonly used by people with cancer [7][8][9], randomized controlled trials of specific therapies in this population rarely demonstrate any benefit in terms of quality of life. Our experience of working in cancer support services leads us to suggest that this is because, for this population especially, the benefits of specific therapies are intertwined with the benefits of the therapeutic relationship and other contextual factors.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary and alternative medicine (CAM) is being increasingly used in Western countries, mainly in a complementary and supportive role after a cancer diagnosis [4,7,16].…”
Section: Introductionmentioning
confidence: 99%